Does a Combination of Virtual Reality, Neuromodulation and Neuroimaging Provide a Comprehensive Platform for Neurorehabilitation? – A Narrative Review of the Literature - Teo, Wei-Peng; Muthalib, Makii; Yamin, Sami; Hendy, Ashlee M.; Bramstedt, Kelly; Kotsopoulos, Eleftheria; Perrey, Stephane; Ayaz, Hasan (Frontiers in Human Neuroscience, 2016)
In the last decade, virtual reality (VR) training has been used extensively in video games and military training to provide a sense of realism and environmental interaction to its users. More recently, VR training has been explored as a possible adjunct therapy for people with motor and mental health dysfunctions. The concept underlying VR therapy as a therapeutic treatment for motor and cognitive dysfunction is to improve plasticity of the brain by engaging users in multisensory training. In this review, we discuss the theoretical framework underlying the use of VR as a therapeutic treatment for neurorehabilitation and provide evidence for its use in treating motor and mental disorders such as cerebral palsy, Parkinson’s disease, stroke, schizophrenia, anxiety disorders and other related clinical areas. While this review provides some insights into the efficacy of VR in clinical rehabilitation, more research is needed to understand how different clinical conditions are affected by VR therapies (e.g., stimulus presentation, interactivity, control and types of VR). Further, there is a lack in robust evidence for the use of VR in clinical populations that is likely due to the inherent nature of the study design used in current research. Future studies should consider large, longitudinal randomized controlled trials to determine the true potential of VR therapies in various clinical populations. While the current literature provides some evidence for the efficacy of VR as an adjunct therapy in clinical rehabilitation, more research is needed to understand how different clinical conditions are affected by VR therapies (e.g., stimulus presentation, interactivity, control and types of VR). Future studies should consider large, longitudinal randomized controlled trials to determine the true potential of VR therapies in various clinical populations.